(untitled) (Bangladesh Journal of Medical Microbiology, 2021)
Background and objectives: Acquiring infection from intensive care units & operation theatres is considered as a significant public health problem around the world. Microbial burden may vary across different ICUs and OTs, albeit these sectors remain underexplored especially in resource poor country. Purpose of the study was qualitative and quantitative assessment of microbial burden in ICUs and OTs’ environmental surfaces of three tertiary care hospitals in Dhaka city. Materials and methods: The study was conducted in the department of Microbiology, BIRDEM General Hospital. A total 232 environmental surface swab samples & 86 hand & nasal swab samples of ICU staffs were collected from the selected three hospitals. The samples were processed according to standard operating procedures. Results: Highest bacterial load from inanimate surface was found on sinks (155 CFU/cm²), ICU bedrails (7.56 ± 0.76 CFU/cm²) and OT sandals (66 CFU/cm²). Pathogenic isolates were found more in ICUs & non-pathogenic isolates were found more in OTs. Among the non-pathogens, Micrococcus spp. (37.8%) and Bacillus spp. (19.8%) were found from OTs. Among the pathogens, Acinetobacter spp. was predominant (21.2%) followed by Pseudomonas spp. (19.2%) in the ICUs. Overall cleanliness & hygiene status of Hospital ‘A’ & ‘C’ were found unacceptable whereas Hospital ‘B’ was found marginally bearable/tolerable. Conclusion: It could be inferred from the study that health care workers and environmental surface contaminations with MDR pathogens are a definitive risk factor for the indoor patients. Routine sampling to assess bioburden in high risk areas of hospital should be done regularly for identification & correction of the weakness of ongoing infection control protocol. Bangladesh J Med Microbiol 2021; 15 (1): 15-25